Hidden treasures: macrophage long non-coding RNAs in lung cancer progression - Karger, Annika; Nandigama, Rajender; Stenzinger, Albrecht; Grimminger, Friedrich; Pullamsetti, Soni Savai; Seeger, Werner; Savai, Rajkumar (Cancers, 2021)
Simple Summary Cancer immunotherapy mainly targets immune system components, such as immune-suppressive networks generated by cancer cells in the tumor microenvironment (TME). Programmed cell death ligand 1, which is a secretory immune-suppressive factor, is released by tumor-associated macrophages (TAMs). The TME also disrupts production of tumor-specific T cells and generates immunosuppressive leukocytes, regulatory T cells, and myeloid-derived suppressor cells. Immune checkpoint inhibitors are effective in various cancers but only in a subset of patients. Non-coding RNAs, such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), are dysregulated in cancer through transcriptional, post-transcriptional, and epigenetic changes and have significant roles in cancer initiation and progression, which depends on deregulation of lncRNA expression. TAM function can be influenced by lncRNAs in various ways. However, our understanding of lncRNA dysregulation and function in cancer remains in the early stage. Ever since RNA sequencing of whole genomes and transcriptomes became available, numerous RNA transcripts without having the classic function of encoding proteins have been discovered. Long non-coding RNAs (lncRNAs) with a length greater than 200 nucleotides were considered as "junk" in the beginning, but it has increasingly become clear that lncRNAs have crucial roles in regulating a variety of cellular mechanisms and are often deregulated in several diseases, such as cancer. Lung cancer is the leading cause of cancer-related deaths and has a survival rate of less than 10%. Immune cells infiltrating the tumor microenvironment (TME) have been shown to have a great effect on tumor development with macrophages being the major cell type within the TME. Macrophages can inherit an inflammatory M1 or an anti-inflammatory M2 phenotype. Tumor-associated macrophages, which are predominantly polarized to M2, favor tumor growth, angiogenesis, and metastasis. In this review, we aimed to describe the complex roles and functions of lncRNAs in macrophages and their influence on lung cancer development and progression through the TME.